Evaluating the effects of pelleting Deoxynivalenol-contaminated dried distillers grains with solubles in the presence of sodium metabisulfite on analyzed DON levels - Frobose, H.L.; Tokach, Michael D.; Hansen, E.L.; McKinney, Leland J.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Deoxynivalenol (DON), also known as vomitoxin, was prevalent in the 2009 U.S. corn crop and subsequently present in dried distillers grains with solubles (DDGS), in which DON levels are about 3 times higher than the original corn source. One method shown to reduce DON levels was by increasing moisture and temperature when sodium bisulfite was added to DON-contaminated corn (Young et al., 19874). Therefore, a pilot study aimed first to replicate these results by placing DON-contaminated DDGS in an autoclave (60 min at 250°F) in the presence of sodium metabisulfite (SMB). The study used 6 treatments: (1) control, (2) 0.5% SMB, (3) 1.0% SMB, (4) 2.5% SMB, (5) 5.0% SMB, and (6) 5.0% SMB with 100 mL/kg water added to evaluate the role of water. After drying, samples were analyzed at North Dakota State University Veterinary Diagnostic Laboratory (NDSU; Fargo, ND). Autoclaving reduced DON levels (R2 = 0.99) with increasing SMB, justifying a follow-up study that aimed to assess whether SMB has the same detoxifying effects on corn DDGS in a commercial pellet mill. For this study, batches of 450 lb DDGS were prepared from DDGS with a known DON concentration (23.4 ppm). The pellet mill was set to a production rate of 1,000 lb/h so retention rate and conditioning temperature could be altered within each batch. Within each batch, 4 samples were collected at conditioning temperatures of 150 and 180°F and retention times of 30 and 60 sec within each temperature. Samples were sent to NDSU for full mycotoxin analysis. No differences (P > 0.15) were found in conditioning temperature or retention time on total DON, DON, or acetyl-DON; however, pelleting DDGS reduced (quadratic; P < 0.01) DON and total DON as SMB increased. Based on these results, the reduction in DON and total DON levels appear to plateau somewhere between SMB levels of 2.5 and 5.0%. These results imply that pelleting in combination with SMB may allow pork producers to utilize DON-contaminated DDGS more effectively, but additional research is required to determine the effect of pelleting SMB in DON-contaminated diets on growth performance of pigs.
Keywords: Swine; Deoxynivalenol; Pelleting; Sodium metabisulfite; Vomitoxin; Nursery pig